Zmiany strategiczne a konkurencyjność przedsiębiorstw na rynku globalnym - Pomykalski, Andrzej (Strategic Changes and Company Competitiveness on Global Markets, 2008)
The author analyzes the impact of competition on business development. The author discusses competitiveness in the light of creating value for an investor and a customer.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 303-308